Aftersound: Mhamad Safa in conversation with Gascia Ouzounian - Safa, M; Ouzounian, G (University of California Press, 2024)
This conversation, which took place at The Showroom, London, on March 8, 2022, brings together the sound producer and architect Mhamad Safa and the sonic theorist Gascia Ouzounian in exploring Safa’s work on sound, trauma, and acoustic jurisprudence, with a focus on Beirut and Lebanon. The conversation covers a range of topics, from the differential policing of noise along lines of social difference; to earwitnessing war and conflict; to the long-term unfolding of auditory forms of trauma and “sonic aftershocks.” Safa and Ouzounian discuss the need for better legal frameworks for confronting the harms of sound; what “collateral damage” might constitute in the context of listening to warfare; and what justice would mean for survivors of sonic violence.